Spectrum of immunodeficiencies with Hodgkin's disease. - Twomey, J J (1980)
The role of six suppressor mechanisms upon T and B cell responses was studied on 17 untreated patients with Hodgkin's disease. Proliferative hyporesponsiveness to mitogen was greatly impaired in 8 of the 13 patients. 10 of these patients had an excessive degree of suppression by cells that adhered to foreign surfaces. Suppression by adherent cells correlated with impairment of proliferative responses and, in some instances, suppression was largely inhibited with indomethacin. Likewise, adherent cells suppressed immunoglobulin synthesis. A correlation was evident between suppression of T and B cell responses by adherent mononuclear leukocytes from individual patients. This suppression coincided with elevated percentages of monocytes in the patient mononuclear cell preparations. This excess of monocytes was not the result of a circulating monocytosis. The monocyte excess may have been acquired during isopyknic cell separation. A second form of suppression was observed in 5 of the 11 patients affected by a lymphocyte that neither adhered to glass wool nor required preactivation. It did not inhibit allogeneic lymphocytes, which contrasts with the suppressor abnormality of monocytoid cells.